1990
DOI: 10.1016/0014-5793(90)80279-r
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of vertebrate brain Na+ and K+ channels by subtypes of protein kinase C

Abstract: Effects of purtfied subtypes I. II and III of protem kmase C (PKC) on voltage-dependent transient K+ (A) and Na+ channels were studied m Xcnopus oocytes injected with chick bram RNA. The experiments were performed in the constant presence of 10 nM p-phorbol 12-myrtstate-13-acetate (PMA) Intracellular injectton of subtype I (5) reduced the A-current (IA). wtth no effect on Na+ current (INa). PKC subtype II (J, +/3,) and III (n) reduced both currents PKC did not affect the response to kainate Inacttvated (heated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…Recently, one ofthe phosphorylation sites ofthe rat Na+ channel a-subunits (a serine residue at position 1506 on the cytoplasmic loop between domains III and IV) was identified as a functional PKC modulation site for Na+ channel activity (West et al,199 1). In this study (West et al,199 1) and others (Lotan et al, 1990;Dascal and Lotan, 199 1;Numann et al, 199 l), diacylglyceride, within minutes, decreased Na+ currents in concert with a slowing of current inactivation. A similar reduction of Na+ currents by the phorbol ester phorbol 12-myristate 13-* PKC Effects on lTX-S and TTX-R Na+ Currents acetate (PMA) has previously been demonstrated in Na+ channels expressed in Xenopus oocytes after injection of chick forebrain mRNA (Sigel and Baur, 1988).…”
Section: Ttx-sensitivesupporting
confidence: 54%
See 2 more Smart Citations
“…Recently, one ofthe phosphorylation sites ofthe rat Na+ channel a-subunits (a serine residue at position 1506 on the cytoplasmic loop between domains III and IV) was identified as a functional PKC modulation site for Na+ channel activity (West et al,199 1). In this study (West et al,199 1) and others (Lotan et al, 1990;Dascal and Lotan, 199 1;Numann et al, 199 l), diacylglyceride, within minutes, decreased Na+ currents in concert with a slowing of current inactivation. A similar reduction of Na+ currents by the phorbol ester phorbol 12-myristate 13-* PKC Effects on lTX-S and TTX-R Na+ Currents acetate (PMA) has previously been demonstrated in Na+ channels expressed in Xenopus oocytes after injection of chick forebrain mRNA (Sigel and Baur, 1988).…”
Section: Ttx-sensitivesupporting
confidence: 54%
“…Both current types displayed a voltage dependence in the effects of PMA. Thus, for both current types steady-state activation (g-v) curves were shifted toward more negative potentials following PMA treatment, resulting in enhanced conductances at activation threshold, whereas steady-state inactivation curves h, were not sig- Vm [mV] currents in astrocytes differ qualitatively from those previously reported for neuronal Na+ channels (Lotan et al, 1990;Dascal and Lotan, 1991;Numann et al, 1991;Schreibmayer et al, 199 1;Li et al, 1992). In those studies using recombinant TTX-S neuronal Na+ channels, PKC activation always reduced peak Na+ currents in concert with an increase in the time constant of current inactivation rl, and a positive shift of steady-state current activation (Dascal and Lotan,199 1).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Protein kinase C is known to modulate the activity of other voltage-activated channels, for example 6, j?-and I/-PKC can decrease transient K+-currents in Xenoyus oocytes, whereas only 01-and /3-PKC reduced transient Na*-currents [21]. Epithelial Cl--channels can be either up-or down-regulated by activation of PKC with either phorbol esters or diacylglycerols [22].…”
Section: Discussionmentioning
confidence: 99%
“…The ubiquitous protein kinase C (PKC) appears to be an especially important modulator of ion channels [4] and has been reported to downmodulate /~, in invertebrate and vertebrate neurons [5][6][7][8][9][10], We have shown that A-channels expressed in Xenopus oocytes from total brain RNA, are regulated by protein kinase C [11]. Now when A-channel clones have been isolated, it is possible to study the molecular mechanisms of their modulation.…”
Section: Introductionmentioning
confidence: 99%